Do statins reduce the risk of myocardial infarction in patients with heart failure? A pooled individual‐level reanalysis of CORONA and GISSI‐HF. (14th February 2015) - Feinstein, Matthew J.; Jhund, Pardeep; Kang, Joseph; Ning, Hongyan; Maggioni, Aldo; Wikstrand, John; Kjekshus, John; Tavazzi, Luigi; McMurray, John; Lloyd‐Jones, Donald M.
<x xml:space="preserve">Abstract</x> Aims Current guidelines do not explicitly recommend statin use in heart failure (HF). Relatively low numbers of atherothrombotic events among HF patients, in the context of their elevated competing risks for non‐atherothrombotic causes of death, may have prevented previous analyses of clinical trials from detecting a benefit for statins. We pooled data from two landmark trials of HF patients not on statin therapy randomized to rosuvastatin 10 mg daily vs. placebo, CORONA and GISSI‐HF, in order to improve our power to detect statistically significant differences in atherothrombotic events. We also accounted for competing risks from other causes of death. Methods and results We used competing risks analyses to evaluate atherothrombotic events in the context of death from other cardiovascular and non‐cardiovascular causes. We also performed traditional Cox survival analyses of the same data with the intention that these statistical approaches would be complementary. CORONA participants (n = 5011, median follow‐up 32.8 months) were older and sicker than GISSI‐HF participants (n = 4574, median follow‐up 46.9 months) by design. Rosuvastatin decreased risk for myocardial infarction (MI) among CORONA and GISSI‐HF participants with ischaemic aetiology of HF (hazard ratio 0.81, 95% confidence interval 0.66–0.99, P < 0.05). There were no significant differences between rosuvastatin and placebo in risks for stroke or death from other causes. Conclusion This individual‐level reanalysis of two landmark trials demonstrates a small but statistically significant decreased risk for MI among patients with ischaemic HF randomized to rosuvastatin vs. placebo. Rosuvastatin appears to be effective in preventing MI in ischaemic HF patients not already on statins.